An Analysis of Buginese Students in Pronouncing English Consonants: A Case Study at English Department Hasanuddin University - Anggi Anggraeni; Kamsinah Kamsinah; Sukmawaty Sukmawaty (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
The aims of this study are: (1) to identify kind of English consonants that are pronounced improperly by Buginese students, and (2) to find out the factors that cause Buginese students in pronouncing English consonants improperly. The method used in this research is descriptive qualitative method. This research is carried out on the Buginese students of English Department of Hasanuddin University batch 2016. The data is obtained by conducting pronunciation test and giving questionnaires. The data is analyzed by identifying the problematic consonants and revealing the factors that caused Buginese students pronounce English consonants improperly. The findings show that the troubled English consonants tend to come from the presence of consonants in English which are not exist in Buginese language such as /θ/, /ð/, /ʃ/, and /tʃ/, the difficulty in distinguishing voiced and voiceless consonants as in /v/ and /z/ sound, and the difficulties related to substitution, omission, and insertion of consonants found in past participle and in plural form. Meanwhile, the causes of the pronunciation problems by Buginese students consist of three causes, namely: the influenced of their mother tongue (Buginese), the period when they start to learn English, and lack of motivation and efforts to make their pronunciation better.